2021
DOI: 10.1891/emdr-d-21-00048
|View full text |Cite
|
Sign up to set email alerts
|

A Model for the Flash Technique Based on Working Memory and Neuroscience Research

Abstract: Research has shown that the Flash Technique (FT) appears to reduce memory-related disturbance and may reduce symptoms of posttraumatic stress disorder. This paper discusses the connections between FT and eye movement desensitization and reprocessing (EMDR) therapy. In FT, clients remind themselves of a traumatic memory without dwelling on it and focus instead on a positive engaging focus and then blink their eyes when prompted. This paper summarizes numerous models describing how the brain processes traumatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
1
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
1
1
0
2
Order By: Relevance
“…Depending on the measurements conducted, there were significant differences between the participants’ scores for traumatic stress in pre-treatment and post-treatment periods and during a one-month follow-up. These results obtained affirm the results of the articles indicating that the EMDR Flash Technique reduces traumatic stress symptoms ( Shebini, 2019 ; Manfield et al, 2021 ; Wong, 2021 ; Yaşar et al, 2021 ) and feature a superiority regarding the greater effectiveness that it showed in comparing a group having the similar traumatic story of socio-demographic and ACE scores such as marital status with a randomized group. It is possible to state that the findings of this study will contribute to the reliability of the EMDR Flash Technique.…”
Section: Discussionsupporting
confidence: 83%
“…Depending on the measurements conducted, there were significant differences between the participants’ scores for traumatic stress in pre-treatment and post-treatment periods and during a one-month follow-up. These results obtained affirm the results of the articles indicating that the EMDR Flash Technique reduces traumatic stress symptoms ( Shebini, 2019 ; Manfield et al, 2021 ; Wong, 2021 ; Yaşar et al, 2021 ) and feature a superiority regarding the greater effectiveness that it showed in comparing a group having the similar traumatic story of socio-demographic and ACE scores such as marital status with a randomized group. It is possible to state that the findings of this study will contribute to the reliability of the EMDR Flash Technique.…”
Section: Discussionsupporting
confidence: 83%
“…In terms of a theory for the mechanism of FT, Wong (2021) proposes that due to over-activation and enhanced connectivity in certain brain structures as a result of PTSD, the client may briefly and reflexively access the distressing memory during the blinking. During that brief access, the amygdala does not have time to react.…”
Section: Discussionmentioning
confidence: 99%
“…To explain the effects of FT in PTSD, Wong (2021) proposes an elaborated model founded on an extrapolation of working memory and neurobiological research. Summarizing the model, the very brief access to the traumatic memory maps in the working memory is only a “reminder of the memory” and prevents the overactivation of the amygdalae.…”
Section: Discussionmentioning
confidence: 99%